2022
DOI: 10.1038/s41598-022-09759-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered hypoxia inducible factor regulation in hereditary haemorrhagic telangiectasia

Abstract: Patients with hereditary haemorrhagic telangiectasia (HHT), also known as Rendu–Osler–Weber syndrome, suffer from the consequences of abnormal vessel structures. These structures can lead to haemorrhages or shunt effects in liver, lungs and brain. This inherited and rare disease is characterized by mutations affecting the transforming growth factor-β (TGF-β)/Bone Morphogenetic Protein (BMP) pathway that results in arteriovenous malformations and studies indicate an impaired immune response. The mechanism under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The reduced expression of HIF-1α in leukocytes of HHT patients may explain some observations of immune defects in HHT patients [ 26 ]. Phosphoglycerate kinase 1 (PGK1) catalyzes the removal of phosphate from 1, 3-bisphosphoglycerate to ADP to form 3-phosphoglycerate and ATP as a sub-step of glycolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced expression of HIF-1α in leukocytes of HHT patients may explain some observations of immune defects in HHT patients [ 26 ]. Phosphoglycerate kinase 1 (PGK1) catalyzes the removal of phosphate from 1, 3-bisphosphoglycerate to ADP to form 3-phosphoglycerate and ATP as a sub-step of glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown immune cell dysfunction in the absence of HIFs [ 24 , 25 ]. Recently, our group quantified, for the first time ever, the expression of HIF-1α and HIF target genes in whole blood samples from HHT patients [ 26 ]. We showed a significant reduction in the expression of HIF1A gene, HIF-1α protein and HIF-1α target genes in whole blood of HHT patients.…”
Section: Introductionmentioning
confidence: 99%